Spanish situation : note on joint meeting of the Labour and Socialist International and International Federation of Trade Unions
1937-01 015b_0017_001 International SPANISH SITUATION. A joint meeting of I.F.T.U. and L.S.I. officers was held in Paris on January 14. At the December conference, it had been decided to issue a manifesto, but in view of the fact that no answer had been obtained officially from the Spanish comrades, giving their decisions regarding the ban on volunteers, etc., it was decided to defer issuing the manifesto. It was likewise reported that the previous day there had been a meeting in Brussels, attended by Adler and Schevenels. There it was demonstrated that a base hospital was urgently needed, costing £15,000, and £1,000 per month for maintenance. The principle of this scheme was approved, and it was left to the officers to be put into operation if it was found financially practical. Schevenels was going to Valencia at the end of the week, when he would interview the Government to get their consent and their help for the project. The advisability of holding a conference in order to discuss the present dangerous international situation and to prevent war was raised by Jouhaux. One suggestion which found approval was that a conference of Governments might be convened by the League of Nations. 292/946/15b/17(i)